VALFORTA: a randomised trial to validate the FORTA (Fit fOR The Aged) classification - Wehling, Martin; Burkhardt, Heinrich; Pazan, Farhad; Throm, Christina; Weiß, Christel (Age & ageing, 2016)
Trial design: to further validate the FORTA (Fit fOR The Aged) concept, a bicentric randomised, controlled trial was run in two geriatric clinics. Methods: patients (≥65 years, ≥3 drugs or ≥60 years, ≥6 drugs) with three relevant diseases and hospitalisation for ≥5 days were randomised. In the intervention, but not the control group, a FORTA team instructed ward physicians on FORTA. FORTA is the first positive/negative listing approach labelling medications used to treat chronic illnesses in older patients from A (indispensable), B (beneficial), C (questionable) to D (avoid). The primary end point was the FORTA score: sum of medication errors classified as over-, under- and mistreatment. Consecutive patients were randomised to the intervention and control ward; outcome assessment was blinded. Results: four hundred and nine patients (age 81.5 years, 64% female, hospitalisation 17.4 days) were included. The primary end point was significantly (P < 0.0001) more reduced in the intervention versus control groups (2.7 ± 2.25 versus 1 ± 1.8, mean ± SD, intergroup comparison of admission/discharge differences). Over- and under-treatment scores and use of A (increase) and D (decrease) drugs were significantly improved (P < 0.01). The total number of adverse drug reactions (ADRs) was significantly reduced by FORTA (P < 0.05, number needed to treat is 5). Activities of daily living and renal failure improved significantly (P < 0.05). Blood pressure remained constant in the intervention, but decreased significantly in the control group. Conclusion: applying FORTA to hospitalised geriatric patients leads to improvement of medication quality and may improve secondary clinical end points (e.g. ADRs). The concept is amenable to successful communication and implementation.
Gesehen am 28.03.2019